Falb ́s critics. Science, religion and politics in bolivian narratives of the remote past during the 1870s and 1880s - Villanueva Criales, Juan (2025)
This paper explores the narratives about the pre-Hispanic past in Bolivia at the end of the 19th century. To do this, it investigates the theses presented in 1878 by the Austrian Rudolf Falb that linked Tiwanaku with the universal flood and three reactions published in Bolivia against these ideas by Pedro José Iturri, Isaac Escobari, and Ignacio Terán. An effort is made to describe the points of disagreement between these authors and Falb and to establish their theoretical roots, social circles, and political affiliations. The result is a complex panorama of influences and theoretical positions, where local scholars postulate different narratives of the remote past. They are related both to their political affiliations around the conservative/religious–liberal/positivist dichotomy and to the gradual production of arguments of rupture between the pre-Hispanic past and contemporary Indigenous people within the framework of modernist projection of the Bolivian nation.